Minimal invasive surgery for patients with urolithiasis with early postoperative rehabilitation in Truskavets - I. Derkach; O. Priyma; A. Loskutov; Ya. Fetsyak; V. Irodenko; O. Petryshyn; M. Bosak; O. Sumtsova; W. Zukow (Kazimierz Wielki University, 2017)
Introduction. Undoubtedly, technological progress, the "conquest" of civilization leads to a deterioration of the environmental situation. It affects the human body, causing a violation of homeostasis, due to disorders in it. The purpose of the work. In view of the above, the task was to study the peculiarities of the process of the use of minimally invasive techniques in patients with urolithiasis treated in the period from 2012 to 2017 in the urological department of the Truskavets City Hospital and in the private office of lithotripsy Ya.V. Feciak in the complex with the use of medical water "Naftusya" during treatment and in the early postoperative period as a means of metaphysics of recurrent stone formation and quicker rehabilitation of patients. Materials and methods of research. The treatment of 1757 patients with urolithiasis in the urological department of Truskavets city hospital and the private office of lithotripsy Ya.V. Fetsiak for the period of 2012 - 2017. The study included 681 patients with kidney stones, 1045 patients - with ureteric stones and 31 patients with urinary bladder specimens. 357 contact nephrolithotripsy, 491 contact ureterolithotripsy (CULT), 27 contact cystolithotripsy and 2074 extracorporeal shock-wave lithotripsy (ESWL) sessions were performed for these patients. Men were 946 (54%), women 811 (46%). The age of the patients ranged from 18 to 84 years. The size of the concretions localized in the ureter ranged from 0.6 cm to 3.4 cm and, as a rule, was 0.9-1.2 cm. The maximum size of the kidney stone was 9.5 cm, and the average size varied within 1 , 4-27cm. ESWL was performed on the Dornier Compact S machine. In the 882 patients, 2074 procedures were carried out for the ESWL, which was 2.35 procedures per patient. In the planned period, 71% of patients, 29% in urgent (at the height of the renal colic or within the next 30 hours) were treated. Results In the contingent of patients treated with ESWL, medical water "Naftusya" was used before the crushing session and exchange course for 2-3 weeks three times a day at a temperature of 17-20 degrees C in an amount of 10 ml per kilogram of weight per day. Patients, who used contact lithotripsy "Naftusya" were prescribed from the second day after the operation, that is, when in the postoperative period, complete peristalsis of the colon was restored. Doses were identical, as in patients with ESWL. Our long experience in treating patients with urolithiasis has shown recurrence of stone formation in 10-15% of patients with urolithiasis within five years of intervention. The latter is much lower compared to the literature without the use of water "Naftusya". Conclusions 1. ESWL - an effective out-patient method of removing concretions from the urinary tract. 2. Contact lithotripsy, along with ESWL - modern methods for the elimination of concretions from urinary tract with short bed day and minimization of surgical trauma. 3. Therapeutic water "Naftusya" - an effective means of metaphysics of urolithiasis. 4. Early postoperative rehabilitation of patients with urolithiasis is possible only on the territory of Truskavets. 5. The use of water "Naftusya" can significantly reduce the recurrence of stone formation in patients with urolithiasis, which makes this balneotherapy a "gold standard" in metaphilactics and early post-operative rehabilitation of patients with urolithiasis.